(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Among the complications of epidural anaesthesia catheter migration is a very rare one. A 45 years old lady was scheduled for repairing of post caesarean incisional hernia. We prefer the hanging drop technique for epidural space identification, and 3 ml air injection to reconfirm the epidural space. After a test dose of 2% lignocaine 2 ml with 10 microgram adrenaline, the catheter was secured with at 3 cm of its length within the epidural space. Immediately after test dose, she complained of lower limb motor lost. On monitor, bradycardia and severe hypotension was shown. Hemodynamic instability was corrected promptly. After proper resuscitation, we aspirate through epidural catheter. CSF was coming freely. We decided to continue with continuous spinal anaesthesia. We assembled a syringe pump. Continuous spinal anaesthesia was maintained with 0.125% bupivacaine @ 3ml/hour DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18158 Journal of BSA, 2010; 23(1): 34-36